Pengaruh Social Influence dan Self Control terhadap Perilaku Menabung Dimediasi Literasi Keuangan Mahasiswa Pendidikan Ekonomi FKIP UNS - Nonik Sindi Rantika; Feri Setyowibowo; Dini Octoria (Departement of Mathematics Education, 2024)
The aim of this research is to determine the influence of social influence and Self-control of saving behavior is mediated by financial literacy of FKIP UNS Economics Education students. The research method used was quantitative with a population of FKIP UNS Economic Education students class 2019 and 2020. The sampling technique used proportionate random sampling with a sample size of 112 respondents. The results of the research prove that (1) there is a positive and significant influence between social influence on financial literacy in FKIP UNS Economic Education students, (2) there is a positive and significant influence between self control on financial literacy among FKIP UNS Economic Education students, (3) there is positive and significant influence between social influence on saving behavior in FKIP UNS Economics Education students, (4) there is a positive and significant influence between self control on saving behavior in FKIP UNS Economics Education students, (5) there is a positive and significant influence between financial literacy on saving behavior among FKIP UNS Economic Education students, and (6) financial literacy cannot mediate social influence and self control on saving behavior among FKIP UNS Economic Education students.